2019
DOI: 10.1161/jaha.119.013248
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffness and Age With Cognitive Performance Decline in the ELSA‐Brasil Cohort

Abstract: Background Increased aortic stiffness has been associated with cognitive decline and dementia, but the results are inconsistent. This study investigated the longitudinal association of aortic stiffness and age with decreased cognitive performance in 3 cognitive tests. Methods and Results This study included 6927 participants, with a mean age of 58.8 years at baseline (2008–2010), who participated in the second wave (2012–2014) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Finally, we did not pool the correlation of aortic PWV and domains of cognitive function in longitudinal studies due to the limited available data. Since there were studies that showed a faster decline in several domains of cognitive function with higher aortic stiffness (Hajjar et al, 2016;Menezes et al, 2019), it would be more convincing if we further confirmed this longitudinal association in our quantitative analysis.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Finally, we did not pool the correlation of aortic PWV and domains of cognitive function in longitudinal studies due to the limited available data. Since there were studies that showed a faster decline in several domains of cognitive function with higher aortic stiffness (Hajjar et al, 2016;Menezes et al, 2019), it would be more convincing if we further confirmed this longitudinal association in our quantitative analysis.…”
Section: Discussionmentioning
confidence: 61%
“…We also calculated the pooled ORs of continuous aortic PWV (m/s) to cognitive impairment or dementia. It showed that the cognitive impairment risk increased 3.9% (OR 1.039; 95% CI 1.005–1.073) per 1 m/s of aortic PWV increase from six studies (15,711 participants) reporting risk of cognitive impairment (Poels et al, 2007 ; Watson et al, 2011 ; Watfa et al, 2015 ; Pase et al, 2016a ; Araghi et al, 2019 ; Menezes et al, 2019 ). There were moderate heterogeneity and no publication bias ( Figure 4 , Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations